PHYSEAL-SPARING DISTAL FEMORAL TROCHLEOPLASTY: A TECHNIQUE ANALYSIS IN A PEDIATRIC CADAVERIC MODEL. Issue 3 (31st March 2019) - Wilson, Philip L.; Ellis, Henry B.; Tompkins, Marc; Stavinoha, Tyler J.; Wyatt, Charles W.; Zynda, Aaron J.; Mitchell, Parker; Jo, Chan-Hee; Shea, Kevin
Background: To describe the results and extra-physeal position of a pediatric distal femoral trochleoplasty in a pediatric cadaveric model. Methods: Eight pediatric cadaveric specimens (mean maturity: 7.75 years, range 4-11) were used to model a distal femoral anterolateral metaphyseal osteotomy immediately proximal to the physis. A standardized 4 mm wedge was placed at the distal end of an anterior cortical shingle; created by an osteotomy 3.25 mm below the anterior cortex (range 2.5 – 4.4), with a transverse corticotomy just proximal to the physis, and hinged 25.5 mm proximally (range 21.9-28.1). The specimens were evaluated with multi-planar micro-CT scans (0.67 mm) pre and post-osteotomy. Lateral cortical elevation, the pre and post sulcus angle of the anterior supra-trochlear metaphysis, distance from distal elevated margin of the osteotomy to the superior edge of the trochlear cartilage, and distance from the distal margin of the osteotomy to the superior edge of the physis were evaluated. Results: The supra-physeal trochleoplasty elevated the lateral cortex an average of 3.26 mm (range 2.8-3.9). The resultant mean angle of the supra-trochlear metaphyseal sulcus was changed by 15.25° (range 8° -21°) (p<0.001); with the central to lateral cortical angle along the anterior femoral surface changing from 173° (range 166°-178°) pre-trochleoplasty, to 157° (range 146°-166°) following the osteotomy. The magnitude of the change in angle was associated with age; with larger corrections in the younger specimens (p<0.05). The distal margin of the trochleoplasty was on average 9.56 mm (range 2.73-13.24) from the superior margin of the trochlear articular cartilage. The distance from the distal extent of the osteotomy to the superior margin of the physis was 5.54 mm (range 1.95-9.55). No fracture into the physis, or physeal deformity was demonstrated. Conclusion: A technique for an extra-physeal, metaphyseal, distal femoral trochleoplasty resulted in alterations to the anterior femoral cortex that may serve as deterrents to lateral patellar translation. Lateral cortical elevation immediately superior to the trochlea may serve as a guide for centralizing patellar motion during early flexion in the setting of patella alta and trochlear dysplasia that is not uncommon in pediatric lateral patellar instability. A pediatric cadaveric model demonstrated changes in close proximity to the superior entrance of the femoral trochlea, while avoiding injury to the distal femoral physis. Significance: A supra-trochlear, lateral metaphyseal elevating osteotomy may be feasible and merit further study as an option for the treatment of lateral patellar instability in the skeletally immature.